The girl on the train [videorecording (DVD)] - Blunt, Emily; Ferguson, Rebecca, 1983-; Bennett, Haley, 1988-; Theroux, Justin; Hawkins, Paula (Universal Pictures Home Entertainment, 2017)
Rachel is unemployed and devastated by a recent divorce. She fills her time with drinking, riding the commuter train, and fantasizing about a seemingly perfect couple the train passes by every day. Then one morning, Rachel sees something shocking that unravels her and entangles her in an unfolding mystery.